Birth Outcomes of Pregnant Women with Anemia in Tertiary Hospital of Rupandehi - Srishti Bajracharya; Sandeep Shakya; Saraj Gurung; Sandeep Shakya; Sharmila Bhandari; Sita Dhakal (Journal of Universal College of Medical Sciences, 2025)
INTRODUCTION Anemia in pregnancy is the commonest medical disorder of pregnancy and a major cause of morbidity and mortality in developing countries like Nepal. It is commonly associated with adverse pregnancy outcomes. Therefore, it is crucial to identify Anemia in pregnancy and its outcomes to improve maternal and fetal care. MATERIAL AND METHODS Cross-sectional study was conducted to find out birth outcomes of pregnant women with Anemia in tertiary hospital of Rupandehi. Two hundred and seventy seven pregnant women without preexisting illnesses before pregnancy admitted in labor ward of Universal College of Medical Sciences- Teaching Hospital (UCMS-TH), Rupandehi were selected by using purposive sampling technique. Data was collected using structured interview schedule and patient’s ANC and inpatient record. Descriptive statistics and inferential statistics were used for analysis with Statistical Package for Social Science (SPSS) software version 16. RESULTS The findings of this study also showed that 32.5% had mild anemia, 6.5% had moderate anemia and 1.8% had severe anemia, 31.9% of respondents with anemia had low birth weight, There was significant association of prevalence of anemia with pregnancy induced hypertension (p=0.004), low birth weight (p<0.001) and meconium stained liquor (p=0.003). There was significant association of prevalence of Anemia with education status (p=0.045), occupation (p<0.001), intake of iron folic acid (p<0.001) and child spacing interval (p=0.019). CONCLUSION The study findings concluded almost half of pregnant women had anemia. Adequate education, counseling and reassurance of the pregnant women for regular birth interval and intake of iron folic acid might increase maternal and perinatal outcomes.